Die Megastruktur von Stăuceni-"Holm", Kreis Botoşani, Rumänien und die Debatte um die Organisation von Cucuteni-Trypillia-Siedlungen / The Mega-structure of Stăuceni-Holm, Botoşani County, Romania, and the Debate About the Organisation of Cucuteni-Trypillia Settlements - Mischka, Doris; Mischka, Carsten; Kovács, Adela; Aparaschivei, Constantin (A haunting spectre. Archaeological studies of social organisation, economic practice, and inequality. A Festschrift for Johannes Müller on the occasion of his 65th birthday, 2025)
Between 2021 and 2023, the Cucuteni A settlement of Stăuceni-“Holm”, Botoşani District in Northeastern Romania, was geophysically surveyed. The settlement is located on a ﬂat promontory with several ditches and palisades delimiting the access from the southern end. Here, a so-called megastructure was partly excavated in 2023. The dwelling is bigger than the other houses at the site and located at a very prominent position close to the probable access of the settlement. The observations, particularly concerning the ﬂoor and wall constructions, provide valuable information for a discussion on the function of such special structures, of which only four have been examined in more detail through excavations thus far. <br
Keywords: Megastructures; Cucuteni-Trypillia; Excavation; Romania